Advances in the treatment of traumatic scars with laser, intense pulsed light, radiofrequency, and ultrasound. Issue 1 (29th January 2019) - Fu, Xiujun; Dong, Jiying; Wang, Shen; Yan, Min; Yao, Min
Abstract: Traumatic scarring is one of the most common complications after soft tissue injury caused by burns and trauma, which affects tens of millions of people worldwide every year. Traumatic scars diminish the quality of life due to disfigurement, symptoms of pain and itch, and restricted motion. The pathogenesis and pathophysiology of traumatic scar remain elusive. The management for traumatic scars is comprised of surgical and non-surgical interventions such as pressure therapy, silicone, corticosteroid, and radiotherapy, which are chosen by clinicians based on the physical examinations of scars. Recently, great progress in treating traumatic scars has been achieved by the development of novel technologies including laser, intense pulsed light (IPL), radiofrequency, and ultrasound. The aim of this review article was to summarize the advances of these technologies for traumatic scars intervention.